Law and the Christian Tradition in Modern Russia - Valliere, Paul (Law and Religion Ser., 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Contributors -- Foreword -- Acknowledgments -- Introduction: A Russian conception of legal consciousness -- Chapter 1 Law and the Orthodox Church in the history of Russia -- Chapter 2 Vasilii Malinovskii: A Russian Christian on war and peace -- Chapter 3 Mikhail Speranskii: Statesman, jurist, and Christian thinker -- Chapter 4 Aleksandr Kunitsyn: Pioneer of natural law in Russia -- Chapter 5 Konstantin Pobedonostsev: Law, religion, and Russian conservatism -- Chapter 6 Boris Chicherin: Christian modernist -- Chapter 7 The civic religion of Anatolii Koni -- Chapter 8 Leonid Kamarovskii: Christian values and international law -- Chapter 9 Vladimir Soloviev: Faith, philosophy, and law -- Chapter 10 Between law and theology: Russia's modern Orthodox canonists -- Chapter 11 Pavel Novgorodtsev: Natural law and its religious justification -- Chapter 12 Sergei Kotliarevskii: The rule of law in Russian liberal theory -- Chapter 13 Nikolai Alekseev: Advocate of social justice and global peace -- Chapter 14 Ivan Ilyin: Philosopher of law, force, and faith -- Afterword -- Index.